Improving the shared value program of Milk Company A - De Leon, Pia Jennylyn B. (Animo Repository, 2017)
This is an action research on Milk Company A. The action research focused on addressing the issue which the lack of concrete plans and roadmap for the implementation of a shared value program to be created by Milk Company A. The objective of the action research are to uncover the true needs of our stakeholders and tailor fit a program that will uplift their knowledge and midwifery skills in the first cycle and to implement a program that will secure exclusive and long term partnership with PPMAP and create an impact to the practice of the midwives and patient care in the second cycle. In addressing the first cycle, my collaborators and I used Lewins Force Field analysis in constructing the issue. Several methods were used to be able to come up with the roadmap such as conducting focus group discussions and tapping the MBA Finance society as the subject matter expert. After creating the plan and roadmap for the modules, the roadmap was not approved by the director of MCA, which is why my collaborators and I went back to planning, implementing and evaluating in the first cycle. After the roadmap was approved, my collaborators and I came up with the issue on how to implement the said roadmap flawlessly. With that, we used the project management framework as our guide in creating the interventions. The program was implemented on April 7, 2017 and it turned out to be a success, in which the midwives were able to apply the knowledge learned in their respective businesses. I learned the different approaches to action research by using tools such as the reflection journals and the ladder of inference. Moreover, this project has helped me to become a true Lasallian business leader who is an agent of change in the community.